Analyzing the influence of automatic steering system on the trajectory tracking accuracy of intelligent vehicle. (July 2018) - Wang, Ruochen; Ye, Qing; Cai, Yingfeng; Wang, Yong; Xu, Xing; Meng, Xiangpeng; Long, Chen
Highlight: A new vision guided IV trajectory tracking control algorithm based on expected yaw velocity is developed to compensate the limitation of traditional vision guided IV trajectory tracking controller in trajectory tracking accuracy and robustness. The back-stepping sliding mode controller is adopted to promote the tracking accuracy and robustness of intelligent vehicle. A new structure of automatic steering system is proposed, and the interference torques models of automatic steering system are established through the mechanism of tire structure. The influence of nonlinear factors of automatic steering system such as the interference torques and time delay on IV trajectory tracking is analyzed through the contrast simulations. Abstract: In this paper, the influence of interference torques, time delay and noise of automatic steering system (ASS) on trajectory tracking accuracy of intelligent vehicle (IV) is analyzed to further study the coupling mechanism between automatic steering control system and IV trajectory tracking control system. The system architecture of ASS and IV trajectory tracking control system is briefly introduced at first. The correlation controller models are then established based on nonlinear ASS and IV dynamic models. The influence of ASS on the trajectory tracking of IV is validated through simulations with various forms of ASS nonlinear factors. And the results show clearly that the interference torques of ASS have great influence on the accuracy of IV trajectory tracking system, especially in the lateral deviation of IV trajectory tracking system, the noise and time delay of ASS have almost no influence on lateral deviation and azimuth deviation of IV trajectory tracking.